ChemInform Abstract: Intramolecular C—C Agostic Complexes: C—C Sigma Interactions by Another Name. Issue 15 (15th April 2014) - Etienne, Michel; Weller, Andrew S.
Abstract Review: developments in the synthesis, characterization and reactivity of metal complexes (s‐, d‐ and f‐block) in which a C—C single bond interacts with a metal center; 112 refs.